2001
DOI: 10.1523/jneurosci.21-20-08091.2001
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Binding Protein Musashi2: Developmentally Regulated Expression in Neural Precursor Cells and Subpopulations of Neurons in Mammalian CNS

Abstract: Musashi1 (Msi1) is a mammalian neural RNA-binding protein highly enriched in neural precursor cells that are capable of generating both neurons and glia during embryonic and postnatal CNS development. Here, we identified Musashi2 (Msi2), a novel mammalian RNA-binding protein that exhibits high sequence similarity to Msi1. The Msi2 transcript appeared to be distributed ubiquitously in a wide variety of tissues, consistent with the mRNA distribution of its Xenopus homolog, xrp1. However, the present study reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

14
267
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 237 publications
(282 citation statements)
references
References 79 publications
14
267
0
1
Order By: Relevance
“…In each case, the sequence can be linked to the identified gene via a contiguous assembly of expressed sequences. The discovery of additional 3Ј UTR sequences is consistent with the fact that a Musashi2 (Msi2h) 3Ј UTR probe detects a 7.1-kb transcript and suggests that the original 2.3-kb Msi2h cDNA sequence (AB056103) is incomplete (30). We also noted that the first 513 base pairs of the original Msi2h cDNA sequence do not align with other Msi2h ESTs or the human MSI2 sequence.…”
Section: Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…In each case, the sequence can be linked to the identified gene via a contiguous assembly of expressed sequences. The discovery of additional 3Ј UTR sequences is consistent with the fact that a Musashi2 (Msi2h) 3Ј UTR probe detects a 7.1-kb transcript and suggests that the original 2.3-kb Msi2h cDNA sequence (AB056103) is incomplete (30). We also noted that the first 513 base pairs of the original Msi2h cDNA sequence do not align with other Msi2h ESTs or the human MSI2 sequence.…”
Section: Resultssupporting
confidence: 72%
“…We have been able to identify three of the ESTs as corresponding to Musashi2, Sox11, and Hrmt1l3. Musashi2 has previously been described as ubiquitously expressed based on Northern analyses of adult tissues (30). However, our in situ hybridization data show that this gene is preferentially expressed in neural tissue in the fetus.…”
Section: Resultsmentioning
confidence: 50%
See 1 more Smart Citation
“…5 The Msi2 gene is located at chromosome 17q22 and has a sequence length of 987 bp. 6 As a RNA-binding protein, Msi2 is linked to stem cells and contribute to asymmetric cell division control, germ and somatic stem cell function, and cell fate determination in a number of tissues.…”
mentioning
confidence: 99%
“…R ecent studies have shown that the Musashi (Msi) family of RNA-binding translational repressors is expressed in proliferative cells of the mammalian central nervous system (1,2), intestine (3), and stomach (4), leading to the proposal that Msi proteins are stem cell markers (5). Despite these observations, a functional requirement for Msi within stem cells has not been demonstrated, largely because of an inability to distinguish stem cells from their immediate daughter cells.…”
mentioning
confidence: 99%